Letter from Carl D. Duncan to Patricia Whiting, March 13, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan thanks Whiting for calling him unexpectedly and mentions attending a concert together. Duncan also compliments Whiting's friend Ron.